The druggable antimalarial target 1-deoxy-D-xylulose-5-phosphate reductoisomerase: purfication, kinetic characterization and inhibition studies,Drugable antimalarial target 1-deoxy-D-xylulose-5-phosphate reductoisomerase - Goble, Jessica Leigh (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
Plasmodium falciparum 1"“deoxy"“D"“xylulose"“5 phosphatereductoisomerase (PfDXR) plays a role in isoprenoid biosynthesis in the malaria parasite and is absent in the human host, making this parasite enzyme an attractive target for antimalarial drug design. To characterize PfDXR, it is necessary to produce large quantities of the enzyme in a soluble and functional form. However, the over"“production of malarial proteins in prokaryotic host systems often results in the formation of truncated proteins or insoluble protein aggregates. A heterologous expression system was developed for the production of active PfDXR using codon harmonization and tight control of expression in the presence of lac repressor. Yields of up to 2 mg/l of enzyme were reported using the optimised expression system, which is 8 to 10"“ fold greater than previously reported yields. The kinetic parameters Km, Vmax and kcat were determined for PfDXR; values reported in this study were consistent with those reported in the literature for other DXR enzymes. A three"“dimensional model of the malarial drug target protein PfDXR was generated, and validated using structure"“checking programs and protein docking studies. Structural and functional features unique to PfDXR were identified using the model and comparative sequence analyses with apicomplexan and non"“apicomplexan DXR proteins. Residues Val44 and Asn45, essential for NADPH binding; and catalytic hatch residues Lys224 and Lys226, which are unique to the species of Plasmodium, were mutated to resemble those of E. coli DXR. Interestingly,these mutations resulted in significant reductions in substrate affinity, when compared to the unmutated PfDXR. Mutant enzymes PfDXR(VN43,44AG) and PfDXR(KK224,226NS) also demonstrated a decreased ability to turnover substrate by 4"“fold and 2"“fold respectively. This study indicates a difference in the role of the catalytic hatch of PfDXR with regards to the way in which it captures substrates. The study also highlights subtle differences in cofactor binding to PfDXR, compared with the well characterized EcDXR enzyme. The validated PfDXR model was also used to develop a novel efficient in silico screening method for potential tool compounds for use in the rational design of novel DXR inhibitors. Following in silico screening of 46 potential DXR inhibitors, a two"“tiered in vitro screening approach was undertaken. DXR inhibition was assessed for the 46 novel compounds using an NADPH"“ ependant DXP enzyme inhibition assay and antimalarial potential was assessed using P.falciparum"“infected erythrocyte growth assays. Select compounds were tested in human cells in order to determine whether they were toxic to the host. From the parallel in silico and in vitro drug screening, it was evident that only a single compound demonstrated reasonable potential binding to DXR (determined using in silico docking), inhibited DXR in vitro and inhibited P. falciparum growth, without being toxic to human cells. Its potential as a lead compound in antimalarial drug development is therefore feasible. Two outcomes were evident from this work. Firstly, analogues of known antimalarial natural products can be screened against malaria, which may then lead towards the rational design of novel compounds that are effective against a specific antimalarial drug target enzyme, such as PfDXR. Secondly, the rational design of novel compounds against a specific antimalarial drug target enzyme can be untaken by adopting a coupled in silico and in vitro approach to drug discovery.
Keywords: Antimalarials -- Development; Plasmodium falciparum; Drug development; Plasmodium falciparum -- Purification; Plasmodium falciparum -- Inhibitors; Enzyme kinetics; Malaria -- Chemotherapy